The trajectories and correlation between physical limitation and depression in elderly residents of Beijing, 1992-2009. - Xia Li; Wei Wang; Qi Gao; Lijuan Wu; Yanxia Luo; Zhe Tang; Xiuhua Guo (PLoS ONE, 2012)
BACKGROUND: Physical limitation and psychological distress have been reported to be related, but studies describing the change of instrumental activities of daily living (IADLs) and depression syndrome over time or exploring the link pattern for their development are limited. The study was to assess distinctive patterns for the development of physical limitation and depression and to explore their correlation to form a proper prevention strategy. METHODS: Dual trajectory analysis was conducted using data from the Beijing Longitudinal Study of Aging (BLSA) 1992-2009 hosted by Xuanwu hospital for subjects with full information on depression and physical limitation for all available visits. Physical limitation was measured by the Instrumental Activities of Daily Living (IADL) scale and depression by the Center for Epidemiological Studies Depression scale (CES-D). The covariates were gender, age at baseline and number of chronic conditions. RESULTS: Three heterogeneous trajectories for physical limitation and two distinct groups for an increase in depression were detected. Among them, 10.13% of subjects experienced an increase in physical limitation, while 13.22% demonstrated a high, stable level of depressive mood. In all, 80.4% of the subjects enjoyed a relatively low, stable level of IADL and CES-D scores. People in the late increase group for IADL score were more likely to have depressive mood when adjusted for gender, age and number of chronic conditions (OR=3.900, 95%CI=1.347-11.290). CONCLUSIONS: The development of physical limitation among the elderly may significantly increase the risk for depressive symptoms.